Preparation method and application of copper oxide coated adriamycin nano material

CN119524015APending Publication Date: 2025-02-28FOURTH MILITARY MEDICAL UNIVERSITY

Patent Information

Application Number
CN202311108180.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The problem of breast cancer's resistance to doxorubicin is that traditional chemotherapy leads to poor targeting of drugs and great toxic and side effects, and requires repeated administration of high doses to improve the therapeutic effect.

Method used

The preparation method of copper-oxidized doxorubicin-laden nanomaterials was adopted to synthesize Cu2O nanoparticles and load doxorubicin into the nanoparticles through ultrasonic dispersion and washing processes to form Cu2O-NH2/DOX nanocomplex.

Benefits of technology

It improves the efficiency and efficacy of drugs, reduces the impact on normal cells, achieves targeted transmission and precise release of drugs, and reduces the side effects of drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524015A_ABST
    Figure CN119524015A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a copper oxide coated adriamycin nano-material, the prepared drug-loaded nano-material has good antitumor activity, and the preparation scheme comprises synthesis of Cu2O nano-particles, synthesis of Cu2O-NH2 nano-particles and drug loading. The copper oxide coated doxorubicin nano-material prepared by the invention can effectively load doxorubicin medicine into nano-particles, so that the medicine transfer efficiency is improved, and the effect of the medicine in vivo is enhanced. The nano material disclosed by the invention can accurately regulate and control the release rate of adriamycin under different buffer solution pH values or different time points, so that the sustained release of the medicine under specific conditions is realized, and the curative effect of the medicine is improved. By modifying the surface of copper oxide, targeted delivery of the medicine can be realized, the medicine can be more accurately delivered to breast cancer cells, the influence on normal cells is reduced, the treatment effect is improved, and the effective service life of the medicine is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of controllable preparation and application of nano materials, and in particular to a preparation method and application of a copper oxide-encapsulated doxorubicin nano material. Background Art

[0002] Breast cancer is the most common malignant tumor in women, surpassing lung cancer to become the world's number one cancer, and the proportion of young patients is increasing year by year. With the proposal and development of the comprehensive diagnosis and treatment model for breast cancer, the treatment methods for breast cancer have become more precise and diverse, but chemotherapy still plays an important role in the treatment options for breast cancer. As the cornerstone drug for chemotherapy of breast cancer, doxorubicin is one of the most widely used drugs, which can play a role by inducing double-strand breaks in the DNA of tumor cells. After traditional chemotherapy is administered, the drug is dispersed through the blood circulation, resulting in poor targeting and low efficacy, and repeated high-dose administration is required to increase the drug concentration in the lesion site. In addition, although doxorubicin has a good chemotherapy effect, the accumulation of doxorubicin in the body can produce serious toxic side effects, such as bone marrow suppression, oral ulcers and severe gastrointestinal reactions; cardiac toxicity can cause delayed severe heart failure, etc. Therefore, the development of a new low-toxic, high-efficiency and highly selective drug delivery system can ensure that chemotherapy drugs play a better role, optimize the treatment effect, and thus improve the quality of life of patients.

[0003] Polymer nanomedicine loads drugs on nanoscale polymer carriers, and kills tumor cells and treats cancer through processes such as in vivo circulation, tumor tissue enrichment and penetration (EPR effect), cell uptake and intracellular drug release. The larger size helps overcome multidrug resistance. Compared with traditional chemotherapy drugs, nano drug carriers have many advantages in drug transportation: ① Improve the water solubility and in vitro and in vivo stability of drugs, enhance drug absorption rate and bioavailability; ② Targeted drug transport, increase drug efficacy, and reduce toxic side effects; ③ Achieve slow and controlled release of drugs, prolong the duration of drug action; ④ Combined drug transport, achieve synergistic therapeutic effects and overcome multidrug resistance. The application of nano drug delivery system has solved the problems of large drug toxicity and side effects and poor drug selectivity in vivo faced by tumor drug treatment to a certain extent.

[0004] Chemodynamic therapy (CDT) is an emerging treatment method that uses the Fenton reaction or Fenton-like reaction to produce highly cytotoxic hydroxyl radicals (·OH), i.e., reactive oxygen species (ROS). Compared with normal cells, cancer cells continuously produce aerobic metabolic byproducts (such as hydrogen peroxide, hydroxyl radicals, and superoxide) caused by carcinogenic transformation, which continuously produce high levels of ROS. Nano drug carriers contain groups such as borate esters, thioketones, sulfides, selenium, and ferrocene, which can enhance the sensitivity to ROS and achieve controlled release of drugs at specific targets. Although many types of tumor cells highly express H2O2, the amount of endogenously produced H2O2 is still difficult to achieve a good chemodynamic therapeutic effect.

[0005] Currently, metal peroxides (MPs) composed of metal ions and peroxide groups are considered to be an effective alternative source of H2O2. 2+ , Cu 2+ , Mn 2+ and Co 2+ Several metal ions such as Cu and Fenton exhibit excellent Fenton catalytic activity, so Fenton-type metal-based MP-NPs are expected to be a simple and promising CDT nanoagent that can self-supply H2O2. In 2019, the National Institutes of Health reported a Fenton-type metal peroxide nanomaterial and confirmed that it can provide H2O2 by itself to enhance the therapeutic effect of CDT. 2+ The coordination effect of CP nanodots can be used to prepare copper peroxide (CP) nanodots, and the coordination effect can be reversed after acid treatment. After being endocytosed by cells, CP nanodots enter tumor cells. The acidic environment of lysosomes accelerates the decomposition of CP nanodots, making the Cu with Fenton catalytic activity 2+ The H2O2 and CP nanodots are released simultaneously, and a Fenton-like reaction occurs to produce ·OH, which kills tumor cells. In addition, small particles of CP nanodots are enriched in tumor tissues after intravenous injection, thereby effectively inhibiting tumor growth. This study not only provides the first example of the preparation of Fenton-type metal peroxide nanomaterials, but also proposes a new strategy to effectively improve the efficiency of CDT.

[0006] Nano-copper oxide has the characteristics of surface effect, quantum size effect, volume effect, and macroscopic quantum tunneling effect, and exhibits unique physical and chemical properties in terms of magnetism, light absorption, chemical activity, thermal resistance, catalysis, etc. As a new type of photoluminescent and nanocatalytic material, copper nanoclusters are increasingly gaining widespread attention in various fields such as photoluminescent analysis, biological probe imaging, and catalysis. This study designed and synthesized a cuprous oxide nanomaterial, which was encapsulated with doxorubicin to form a Cu2O-NH2 / DOX nanocomposite, showing its potential ability to fight breast cancer. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a method for preparing and applying a copper oxide-encapsulated doxorubicin nanomaterial to address the problem of doxorubicin resistance in breast cancer. The prepared drug-loaded nanomaterial has good anti-tumor activity.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial, comprising the following steps:

[0010] a. Synthesis of Cu2O nanoparticles:

[0011] 0.5 mmol CuCl2·2H2O and 0.5 g polyvinyl pyrrolidone (PVP) were dissolved in 200 mL deionized water and stirred at room temperature. NaOH solution and ascorbic acid were added and stirred to react to obtain Cu2O nanoparticles, which were washed and freeze-dried for storage.

[0012] b. Synthesis of Cu2O-NH2 nanoparticles:

[0013] 100 mg of Cu2O nanoparticles and 500 uL of 3-aminopropyltriethoxysilane were dispersed in 60 mL of ethanol, refluxed and washed, freeze-dried and stored to synthesize Cu2O-NH2 nanoparticles.

[0014] c. Drug loading:

[0015] Cu2O-NH2 nanoparticles and different concentrations of DOX were ultrasonically dispersed in phosphate buffer (PBS) at pH 7.4 and centrifuged after stirring. The unloaded DOX was washed and removed. The UV-visible spectra of Cu2O nanoparticles before and after loading with DOX were recorded to determine the drug loading amount. The absorption peak at 480 nm was used to determine the DOX concentration.

[0016] As a further embodiment of the present invention, when synthesizing Cu2O nanoparticles, 0.5 mmol CuCl2·2H2O and 0.5 g polyvinylpyrrolidone (PVP) were dissolved in 200 mL deionized water, stirred at room temperature for 5 minutes, 12.5 mL NaOH solution was added, stirring was continued for 5 minutes, 12.5 mL ascorbic acid was added dropwise and stirring was continued for 10 minutes to obtain yellow Cu2O nanoparticles.

[0017] As a further embodiment of the present invention, the molar concentration of the NaOH solution is 0.2M, and the molar concentration of ascorbic acid is 0.1M.

[0018] As a further embodiment of the present invention, when synthesizing Cu2O nanoparticles, washing and freeze-drying for storage for later use comprises: washing the Cu2O nanoparticles with ethanol and deionized water by centrifugation for 3 times, wherein the centrifugal speed is 9500rpm / 10min, and finally freeze-drying the Cu2O nanoparticles and storing them in a 4°C environment for later use.

[0019] As a further embodiment of the present invention, when synthesizing Cu2O-NH2 nanoparticles, Cu2O nanoparticles and 3-aminopropyltriethoxysilane are dispersed in 60 mL of ethanol, ultrasonicated for 10 minutes, then refluxed at 110°C for 12 hours, then centrifuged and washed three times with ethanol and deionized water, and finally freeze-dried and stored in a 4°C environment for future use.

[0020] As a further embodiment of the present invention, when loading drugs, the concentration of Cu2O-NH2 nanoparticles is 0.2 mg / mL, and the different concentrations of DOX are 0.5 mg / mL, 1.0 mg / mL, 2.0 mg / mL, and 4.0 mg / mL, respectively.

[0021] As a further embodiment of the present invention, when centrifuging after stirring, washing and removing unloaded DOX, after stirring at room temperature for 24 hours, the complex was collected by centrifugation at 9500 rpm for 10 minutes and washed 4 times with PBS (pH 7.4) to remove excess unloaded DOX.

[0022] As a further embodiment of the present invention, the drug loading is calculated according to the following formula:

[0023] Drug loading = m(loaded doxorubicin) / m(Cu2O)×100%.

[0024] A drug delivery method using the copper oxide-encapsulated doxorubicin nanomaterial comprises applying the nanomaterial to cancer treatment.

[0025] As a further embodiment of the present invention, the release rate of the drug can be regulated in buffer solutions with different pH values, and the release rate of the drug can also be regulated according to time.

[0026] A method for treating breast cancer comprises applying the copper oxide-encapsulated doxorubicin nanomaterial to breast cancer cells.

[0027] A method for evaluating the effect of a drug on breast cancer cells comprises applying the copper oxide-encapsulated doxorubicin nanomaterial to breast cancer cells to evaluate its cytotoxicity.

[0028] A method for preparing a copper oxide-encapsulated doxorubicin nanomaterial, wherein the DOX concentration in the preparation step can be adjusted as required.

[0029] Compared with the prior art, the present invention provides a preparation method and application of a copper oxide-encapsulated doxorubicin nanomaterial formulation, which has the following beneficial effects:

[0030] 1. Efficient drug delivery: The copper oxide-encapsulated doxorubicin nanomaterial prepared by the present invention can effectively load doxorubicin into nanoparticles, improve drug delivery efficiency, and help enhance the effect of the drug in the body.

[0031] 2. Precisely control release: The nanomaterial of the present invention can precisely regulate the release rate of doxorubicin at different pH values ​​of buffer solutions or at different time points, thereby achieving sustained release of the drug under specific conditions and improving the efficacy of the drug.

[0032] 3. Targeted therapy: By modifying the surface of copper oxide, targeted drug delivery can be achieved, and the drug can be delivered to breast cancer cells more accurately, reducing the impact on normal cells and improving the treatment effect.

[0033] 4. Adjustable drug concentration: By adjusting the concentration of doxorubicin in Cu2O-NH2 nanoparticles, the treatment plan can be flexibly adjusted according to the needs of the disease and the side effects of the drug can be minimized.

[0034] In summary, the preparation method of the copper oxide-encapsulated doxorubicin nanomaterial of the present invention and its application have important practical application value in the field of drug delivery and cancer treatment. The preparation process is simple, avoids cumbersome preparation process, and reduces preparation cost. In addition to its application in breast cancer treatment, the drug delivery and release characteristics of the nanomaterial of the present invention also make it have broad application prospects in other cancer treatment and drug delivery fields. By encapsulating doxorubicin in copper oxide nanoparticles, the stability of the drug can be improved, the degradation and inactivation of the drug can be reduced, and the effective service life of the drug can be extended. The present invention can provide a more effective and accurate drug treatment plan, bringing better treatment effect and quality of life to patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of a chemical reaction formula for synthesizing nanomaterials in a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention;

[0036] Figure 2 It is a schematic diagram of the results of XRD testing in a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention.

[0037] Figure 3 It is a schematic diagram of the particle size of a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention.

[0038] Figure 4The present invention provides a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention, and a schematic diagram of the CuO-NH2-DOX morphology observed by TEM in the microscopic morphology of the nano drug-carrying material.

[0039] Figure 5 The present invention provides a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula, which shows a schematic diagram of the CuO-NH2 morphology in the nano drug-carrying material observed by TEM.

[0040] Figure 6 The present invention provides a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention, and shows a schematic diagram of the CuO morphology in the nano drug-carrying material, the microscopic morphology of which is observed by TEM.

[0041] Figure 7 It is a schematic diagram of the results of Fourier infrared spectrometer testing in a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention.

[0042] Figure 8 It is a schematic diagram of the result of measuring the material potential by a particle size potential analyzer in the preparation method of a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention.

[0043] Fig. 9 It is a schematic diagram of the results of X-ray photoelectron spectroscopy testing of Cu2O in a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention.

[0044] Fig.10 It is a schematic diagram of the results of X-ray photoelectron spectroscopy testing of Cu2P in a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention.

[0045] Fig.11 It is a schematic diagram of the results of a cytotoxicity experiment of a non-drug-loaded material in a method for preparing a copper oxide-loaded doxorubicin nanomaterial formula provided by the present invention.

[0046] Fig.12 It is a schematic diagram of the results of a normal cytotoxicity experiment of the nanomaterial loaded with doxorubicin in a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention.

[0047] Fig.13 It is a schematic diagram of the results of the MDA-MB-231 cytotoxicity experiment of the nanomaterial loaded with doxorubicin in the preparation method of the copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention.

[0048] Fig.14It is a schematic diagram of the results of a T47D cell toxicity experiment of the nanomaterial loaded with doxorubicin in a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial formula provided by the present invention.

[0049] Fig.15 It is a schematic diagram of doxorubicin loading of a nano drug-carrying material in a method for preparing a copper oxide-encapsulated doxorubicin nano material formula provided by the present invention. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention is clearly and completely described below in combination with examples. The described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Currently, metal peroxides (MPs) composed of metal ions and peroxide groups are considered to be an effective alternative source of H2O2. 2+ , Cu 2+ , Mn 2+ and Co 2+ Several metal ions such as Cu and Fenton exhibit excellent Fenton catalytic activity, so Fenton-type metal-based MP-NPs are expected to be a simple and promising CDT nanoagent that can self-supply H2O2. In 2019, the National Institutes of Health reported a Fenton-type metal peroxide nanomaterial and confirmed that it can provide H2O2 by itself to enhance the therapeutic effect of CDT. 2+ The coordination effect of CP nanodots can be used to prepare copper peroxide (CP) nanodots, and the coordination effect can be reversed after acid treatment. After being endocytosed by cells, CP nanodots enter tumor cells. The acidic environment of lysosomes accelerates the decomposition of CP nanodots, making the Cu with Fenton catalytic activity 2+ The H2O2 and CP nanodots are released simultaneously, and a Fenton-like reaction occurs to produce ·OH, which kills tumor cells. In addition, small particles of CP nanodots are enriched in tumor tissues after intravenous injection, thereby effectively inhibiting tumor growth. This study not only provides the first example of the preparation of Fenton-type metal peroxide nanomaterials, but also proposes a new strategy to effectively improve the efficiency of CDT.

[0052] Nano-copper oxide has the characteristics of surface effect, quantum size effect, volume effect, and macroscopic quantum tunneling effect, and exhibits unique physical and chemical properties in terms of magnetism, light absorption, chemical activity, thermal resistance, catalysis, etc. As a new type of photoluminescent and nanocatalytic material, copper nanoclusters are increasingly gaining widespread attention in various fields such as photoluminescent analysis, biological probe imaging, and catalysis. This study designed and synthesized a cuprous oxide nanomaterial, which was encapsulated with doxorubicin to form a Cu2O-NH2 / DOX nanocomposite, showing its potential ability to fight breast cancer.

[0053] The invention provides a preparation method and application of a copper oxide-encapsulated doxorubicin nanomaterial. The prepared drug-loaded nanomaterial has good anti-tumor activity.

[0054] In the present invention, see Figure 1 As shown, the preparation method of the copper oxide-encapsulated doxorubicin nanomaterial comprises the following steps:

[0055] a. Synthesis of Cu2O nanoparticles:

[0056] 0.5 mmol CuCl2·2H2O and 0.5 g polyvinylpyrrolidone (PVP) were dissolved in 200 mL deionized water and stirred at room temperature. NaOH solution and ascorbic acid were added and stirred to react to obtain Cu2O nanoparticles, which were washed and freeze-dried for storage.

[0057] b. Synthesis of Cu2O-NH2 nanoparticles:

[0058] 100 mg of Cu2O nanoparticles and 500 uL of 3-aminopropyltriethoxysilane were dispersed in 60 mL of ethanol, refluxed and washed, freeze-dried and stored to synthesize Cu2O-NH2 nanoparticles.

[0059] c. Drug loading:

[0060] Cu2O-NH2 nanoparticles and different concentrations of DOX were ultrasonically dispersed in phosphate buffer (PBS) at pH 7.4 and centrifuged after stirring. The unloaded DOX was washed and removed. The UV-visible spectra of Cu2O nanoparticles before and after loading with DOX were recorded to determine the drug loading amount. The absorption peak at 480 nm was used to determine the DOX concentration.

[0061] In step a of the present invention, when synthesizing Cu2O nanoparticles, 0.5 mmol CuCl2·2H2O and 0.5 g polyvinylpyrrolidone (PVP) are dissolved in 200 mL deionized water, stirred at room temperature for 5 minutes, 12.5 mL NaOH solution is added, stirring is continued for 5 minutes, 12.5 mL ascorbic acid is added dropwise and stirring is continued for 10 minutes to obtain yellow Cu2O nanoparticles.

[0062] Wherein, the molar concentration of the NaOH solution is 0.2M, and the molar concentration of ascorbic acid is 0.1M.

[0063] In step b of the present invention, when synthesizing Cu2O nanoparticles, washing and freeze-drying for storage for later use comprises: washing the Cu2O nanoparticles with ethanol and deionized water by centrifugation for 3 times, wherein the centrifugal speed is 9500rpm / 10min, and finally freeze-drying the Cu2O nanoparticles and storing them in a 4°C environment for later use.

[0064] When synthesizing Cu2O-NH2 nanoparticles, Cu2O nanoparticles and 3-aminopropyltriethoxysilane were dispersed in 60 mL of ethanol, ultrasonicated for 10 minutes, and then refluxed at 110°C for 12 hours, then centrifuged and washed three times with ethanol and deionized water, and finally freeze-dried and stored in a 4°C environment for future use.

[0065] In step c of the present invention, when loading drugs, the concentration of Cu2O-NH2 nanoparticles is 0.2 mg / mL, and the different concentrations of DOX are 0.5 mg / mL, 1.0 mg / mL, 2.0 mg / mL, and 4.0 mg / mL, respectively.

[0066] When the unloaded DOX was washed and removed by centrifugation after stirring, the complex was collected by centrifugation at 9500 rpm for 10 minutes after stirring at room temperature for 24 hours, and washed 4 times with PBS (pH 7.4) to remove excess unloaded DOX.

[0067] The drug loading is calculated according to the following formula:

[0068] Drug loading = m(loaded doxorubicin) / m(Cu2O)×100%.

[0069] The preparation method of the copper oxide-encapsulated doxorubicin nanomaterial formula of the present invention has the effects of efficient drug delivery, precise control of release, targeted therapy and adjustable drug concentration. The copper oxide-encapsulated doxorubicin nanomaterial prepared by the present invention can effectively load doxorubicin drugs into nanoparticles, improve drug delivery efficiency, and help enhance the effect of the drug in the body. The nanomaterial of the present invention can accurately regulate the release rate of doxorubicin at different pH values ​​of buffer solutions or at different time points, thereby achieving sustained release of the drug under specific conditions and improving the efficacy of the drug. By modifying the surface of copper oxide, targeted delivery of drugs can be achieved, and the drugs can be more accurately delivered to breast cancer cells, reducing the impact on normal cells and improving the therapeutic effect. By adjusting the concentration of doxorubicin in the Cu2O-NH2 nanoparticles, the treatment plan can be flexibly adjusted according to the needs of the disease, and the side effects of the drug can be minimized.

[0070] Therefore, see Figure 1As shown, the preparation process of the novel copper oxide-encapsulated doxorubicin nanomaterial (Cu2O-NH2 / DOX) in the preparation method of the copper oxide-encapsulated doxorubicin nanomaterial formula of the present invention is as follows:

[0071] (1) Cu2O synthesis method: 0.5 mmol CuCl2.2H2O, 0.5 g polyvinyl pyrrolidone (PVP) were dissolved in 200 mL deionized water and stirred at room temperature for 5 minutes. Then, 12.5 mL NaOH solution (0.2 M) was added and stirred for 5 minutes. Then, 12.5 mL ascorbic acid (0.1 M) was slowly added dropwise to the above system and stirred for 10 minutes to obtain yellow Cu2O nanoparticles. The product was then centrifuged and washed three times with ethanol and deionized water (9500 rpm / 10 min). Finally, the Cu2O nanoparticles were freeze-dried and stored at 4°C for future use.

[0072] (2) Cu2O-NH2 synthesis method: 100 mg Cu2O nanoparticles and 500 uL 3-aminopropyltriethoxysilane (APTES) were dispersed in 60 mL ethanol, ultrasonicated for 10 min, then refluxed at 110 °C for 12 h, then washed three times by centrifugation with ethanol and deionized water, and finally freeze-dried and stored at 4 °C for future use.

[0073] (3) DOX loading method: Cu2O-NH2 nanoparticles (0.2 mg / mL) were mixed with different concentrations of DOX (0.5, 1.0, 2.0, 4.0 mg / mL) in phosphate buffered saline (PBS) at pH 7.4 and dispersed evenly by ultrasound. After stirring at room temperature for 24 hours, the complex was collected by centrifugation at 9500 rpm for 10 minutes and washed 4 times with PBS (pH 7.4) to remove excess unloaded DOX. The UV-visible spectra of Cu2O nanoparticles before and after DOX loading were recorded to determine the drug loading. The absorption peak at 480 nm was used to determine the DOX concentration. The drug loading was calculated as follows: m(loaded doxorubicin) / m(Cu2O)×100%.

[0074] In summary, the preparation method of the copper oxide-encapsulated doxorubicin nanomaterial of the present invention and its application have important practical application value in the field of drug delivery and cancer treatment. The preparation process is simple, avoids cumbersome preparation process, and reduces preparation cost. In addition to its application in breast cancer treatment, the drug delivery and release characteristics of the nanomaterial of the present invention also make it have broad application prospects in other cancer treatment and drug delivery fields. By encapsulating doxorubicin in copper oxide nanoparticles, the stability of the drug can be improved, the degradation and inactivation of the drug can be reduced, and the effective service life of the drug can be extended. The present invention can provide a more effective and accurate drug treatment plan, bringing better treatment effect and quality of life to patients.

[0075] The present invention also provides a drug delivery method using the copper oxide-encapsulated doxorubicin nanomaterial, including applying the nanomaterial to cancer treatment, wherein the drug release rate can be regulated in buffer solutions with different pH values, and the drug release rate can also be regulated according to time.

[0076] The present invention also provides a method for treating breast cancer, comprising applying the copper oxide-encapsulated doxorubicin nanomaterial to breast cancer cells.

[0077] The present invention also provides a method for evaluating the effect of a drug on breast cancer cells, comprising applying the copper oxide-encapsulated doxorubicin nanomaterial to breast cancer cells to evaluate its cytotoxicity.

[0078] The present invention also provides a method for preparing a copper oxide-encapsulated doxorubicin nanomaterial, and the DOX concentration in the preparation step can be adjusted as needed.

[0079] In the present invention, the characterization of the nano drug-carrying material includes:

[0080] (1) See Figure 2 As shown, the material phase is tested by XRD: the X-ray radiation source is Cu-Kα, and the scanning range is 5-70°.

[0081] (2) Particle size: Take an appropriate amount of nanocarriers and add them to deionized water, disperse them by ultrasonic, and prepare 5 mL of nanocarrier suspension with a volume fraction of about 0.2 g / L. Use a dynamic light scattering instrument to measure the particle size of the nanocarriers, and set the measurement time to 2 min. Figure 3 shown.

[0082] (3) Observation of microscopic morphology using TEM: Transmission electron microscopy (TEM) is used to observe the morphology and size of the sample. Sample preparation process: The nanocarrier prepared above is dispersed in anhydrous ethanol and ultrasonicated for 30 minutes. The copper mesh carbon support film is dipped in the liquid and dried naturally at 25°C to obtain CuO-NH2-DOX. Figure 4 As shown, the CuO-NH2 morphology can be found in Figure 5 As shown, the CuO morphology can be found in Figure 6 shown.

[0083] (4) Drug loading: The absorbance of the material and the composite material system after drug loading was tested by ultraviolet spectrophotometer. 5 mg of doxorubicin hydrochloride was added to 3 mL of phosphate buffer solution (PH = 7.4), ultrasonically dissolved, and 15 mg of nanocarriers were added. The mixture was magnetically stirred for 24 h and centrifuged at 9000 r for 10 min. The mixture was washed with phosphate buffer solution (PH 7.4), and the supernatant was collected and placed in a 50 mL volumetric flask. After the volume was fixed, the absorbance of the supernatant was measured at a wavelength of 480 nm to calculate the mass of doxorubicin hydrochloride loaded in the carrier.

[0084] (5) See Figure 7 As shown, the structure was verified by using a Fourier transform infrared spectrometer to test the infrared absorption spectrum of the material, with a scanning range of 400-4000cm-1 and 20 scans.

[0085] (6) See Figure 8 As shown, the material potential was measured using a particle size potential analyzer: a certain amount of different nanocarriers were weighed and dissolved in PBS solutions of different pH values ​​(pH 7.4 or 6.8), oscillated on a constant temperature oscillator at 37°C for 2 hours, and the Zeta potential was measured using a particle size analyzer.

[0086] (7) See Fig. 9 and Fig.10 As shown, the main application of X-ray photoelectron spectroscopy technology, XPS, is to determine the binding energy of electrons to identify the chemical properties and composition of the sample surface.

[0087] In this embodiment, see Fig.15 As shown, the drug release capacity of doxorubicin of nano drug-carrying material is determined: the carrier is added to 3mL phosphate buffer solution (PH7.4), and vortexed to disperse evenly. Take 500uL of the dispersion into a dialysis bag, and place it in 100ml of two buffer solutions of PH5.0 and 7.4 respectively and oscillate (37°C, 100r / min). At the predetermined time points (1, 2, 4, 6, 8, 12, 24, 48, 72, 96, 120, 144h), 5mL of dissolution medium is taken out, and an equal volume of dissolution medium is added at the same time, and the absorbance value is measured at a wavelength of 480nm, and the DOX release in different buffer solutions is calculated respectively. In addition, as a control, the drug release of free DOX under pH 7.4 conditions is determined at the same time.

[0088] Evaluation of the effect of drug-loaded materials on breast cancer cells: Cytotoxicity test. For the cytotoxicity test of non-drug-loaded materials, see Fig.11 As shown in Figure 2, the cytotoxicity of the nanomaterials without doxorubicin loading to normal fibroblasts HT1080 and breast cancer cells MDA-MB-231 / T47D was minimal. Figure 12 to Figure 14 As shown, the cytotoxicity of the nanomaterials loaded with doxorubicin to normal cells HT1080 is very small, and the cytotoxicity of the nanomaterials loaded with doxorubicin to breast cancer cells is dependent on the dose of doxorubicin.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A copper oxide-loaded doxorubicin nanomaterial, characterized in that: The following steps are involved: a. Synthesis of Cu2O nanoparticles: 0.5 mmol CuCl2·2H2O and 0.5 g polyvinyl pyrrolidone (PVP) were dissolved in 200 mL deionized water, stirred at room temperature, and NaOH solution and ascorbic acid were added. After stirring and reacting, Cu2O nanoparticles were obtained, which were washed and freeze-dried for storage; b. Synthesis of Cu2O-NH2 nanoparticles: 100 mg Cu2O nanoparticles and 500 uL 3-aminopropyltriethoxysilane were dispersed in 60 mL ethanol, refluxed, washed, freeze-dried and stored to synthesize Cu2O-NH2 nanoparticles; c. Drug loading: Cu2O-NH2 nanoparticles and different concentrations of DOX were ultrasonically dispersed in phosphate buffer (PBS) at pH 7.4 and centrifuged after stirring. The unloaded DOX was washed and removed. The UV-visible spectra of Cu2O nanoparticles before and after loading with DOX were recorded to determine the drug loading amount. The absorption peak at 480 nm was used to determine the DOX concentration.

2. The copper oxide-loaded doxorubicin nanomaterial according to claim 1, characterized in that: When synthesizing Cu2O nanoparticles, 0.5mmol CuCl2·2H2O and 0.5g polyvinyl pyrrolidone were dissolved in 200mL deionized water, stirred at room temperature for 5 minutes, 12.5mL NaOH solution was added, and stirring was continued for 5 minutes. 12.5mL ascorbic acid was added dropwise and stirring was continued for 10 minutes to obtain yellow Cu2O nanoparticles.

3. The copper oxide-loaded doxorubicin nanomaterial according to claim 2, characterized in that: The molar concentration of the NaOH solution is 0.2M, and the molar concentration of ascorbic acid is 0.1M.

4. The copper oxide-loaded doxorubicin nanomaterial according to claim 3, characterized in that: When synthesizing Cu2O nanoparticles, washing and freeze-drying for storage for later use includes: washing the Cu2O nanoparticles with ethanol and deionized water by centrifugation for 3 times, wherein the centrifugal speed is 9500rpm / 10min, and finally freeze-drying the Cu2O nanoparticles and storing them in a 4°C environment for later use.

5. The copper oxide-loaded doxorubicin nanomaterial according to claim 4, characterized in that: When synthesizing Cu2O-NH2 nanoparticles, Cu2O nanoparticles and 3-aminopropyltriethoxysilane were dispersed in 60 mL of ethanol, ultrasonicated for 10 minutes, and then refluxed at 110°C for 12 hours, then centrifuged and washed three times with ethanol and deionized water, and finally freeze-dried and stored in a 4°C environment for future use.

6. The copper oxide-loaded doxorubicin nanomaterial according to claim 1, characterized in that: When loading drugs, the concentration of Cu2O-NH2 nanoparticles was 0.2 mg / mL, and the different concentrations of DOX were 0.5 mg / mL, 1.0 mg / mL, 2.0 mg / mL, and 4.0 mg / mL.

7. The copper oxide-loaded doxorubicin nanomaterial according to claim 6, characterized in that: After stirring and centrifugation, the unloaded DOX was washed and removed. After stirring at room temperature for 24 h, the complex was collected by centrifugation at 9500 rpm for 10 min and washed 4 times with phosphate buffer to remove excess unloaded DOX.

8. The copper oxide-loaded doxorubicin nanomaterial according to claim 7, characterized in that: The pH value of the phosphate buffer is 7.

4.

9. The copper oxide-loaded doxorubicin nanomaterial according to claim 1, characterized in that: The calculation formula of drug loading is: Drug loading = m(loaded doxorubicin) / m(Cu2O)×100%.

10. A drug delivery method using the copper oxide-encapsulated doxorubicin nanomaterial according to any one of claims 1 to 9, characterized in that: The nanomaterial is applied to cancer treatment, and the drug release rate is regulated in buffer solutions with different pH values, or regulated according to time.

Citation Information

Patent Citations

  • Preparation of polyhedral cuprous oxide nano particle

    CN101348275A

  • Preparation method of temperature triggered drug-loading copper sulfide nanocage

    CN108853494A

  • Controlled-release nano-drug carrier as well as preparation method and application thereof

    CN112516321A

  • ICG-MSNs nano material and preparation method and application thereof

    CN113144216A

  • Nano-drug for treating osteoporosis as well as preparation method and application of nano-drug

    CN114129587A

Cited By

  • Nanoscale coordination polymer NP (at) DoxCu based on copper ions and doxorubicin as well as preparation method and application of nanoscale coordination polymer NP (at) DoxCu

    CN120713846A